(Invited) Graphene Synthesis and Processing on Ge Substrates. (18th August 2016) - Lukosius, Mindaugas; Lippert, Gunther; Dabrowski, J; Kitzmann, Julia; Lisker, Marco; Kulse, P; Krüger, Andreas; Fursenko, Oksana; Costina, Ioan; Trusch, Andreas; Yamamoto, Yuji; Wolff, Andre; et al.
Abstract : We review some of the recent results obtained on the graphene synthesis on Ge(100)/Si(100) substrates by molecular beam epitaxy and wafer scale chemical vapor deposition. We outline some of the identified challenges in synthesis and present first experimental results on patterning and in-line metrology of graphene in a 200 mm wafer pilot line.